(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to know the impact of the servant leadership in the organizational immune system in the Ministry of Planning, as the analytical approach was adopted in carrying out this research, and the research community included the administrative leaderships of the Ministry of Planning in the city of Baghdad, while the research sample was (Director general and his assistants, Department head, Division official ) as an intentional sample for the research community in (Ministry Center, Central Statistical Organization, Central Organization for Standardization and Control and Administrative Development Center) and the comprehensive inventory, as the researcher distributed (220) questionnaires, and then collected data from (172) respondents from the community researched by accreditation The questionnaire, which included (47) items And provide them with personal interviews and field observations as tools to help strengthen them. The research adopted the program (Amos V.23, SPSS V.23) by adopting appropriate statistical methods. The results showed the validity of the correlation and influence relationships at the level of the main and sub-research variables, indicating the essential role of servant leadership in influencing the organizational immune system in the Ministry of Planning.